2022
DOI: 10.1002/eat.23883
|View full text |Cite
|
Sign up to set email alerts
|

Examining changes in binge‐eating disorder network centrality and structure in patients treated with cognitive‐behavioral therapy versus interpersonal psychotherapy

Abstract: Objective: A sizeable minority of patients with binge-eating disorder (BED) do not fully respond to evidence-based treatments. Evidence to guide refinements of treatments is needed. Conceptualizing BED as arising from a network of symptomto-symptom interactions allows for identification of the most strongly connected symptoms, which could inform intervention targets. This study estimated networks of BED features at pretreatment and posttreatment to assess whether cognitive behavioral therapy (CBT) and interper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…At the global level, network theory-predicted reductions in network connectivity in response to treatment were found for one study (Calugi, Dametti, Chimini, Dalle Grave, & Dalle Grave, 2021), yet non-significant differences (Forrest & Grilo, 2022 baseline v. post-intervention comparison;Forrest et al, 2023;Smith et al, 2019) or increases in overall connectivity (Forrest & Grilo, 2022 baseline v. follow-up comparison;Hilbert et al, 2020) were found in others. Smith et al (2019) also found in a transdiagnostic sample that treatment non-responders had greater network connectivity at pre-intervention relative to responders, but this effect was not found by Hilbert et al (2020) among a binge eating disorder sample.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…At the global level, network theory-predicted reductions in network connectivity in response to treatment were found for one study (Calugi, Dametti, Chimini, Dalle Grave, & Dalle Grave, 2021), yet non-significant differences (Forrest & Grilo, 2022 baseline v. post-intervention comparison;Forrest et al, 2023;Smith et al, 2019) or increases in overall connectivity (Forrest & Grilo, 2022 baseline v. follow-up comparison;Hilbert et al, 2020) were found in others. Smith et al (2019) also found in a transdiagnostic sample that treatment non-responders had greater network connectivity at pre-intervention relative to responders, but this effect was not found by Hilbert et al (2020) among a binge eating disorder sample.…”
Section: Introductionmentioning
confidence: 94%
“…increased connections to other symptoms in the network) rather than a reduction in line with diminished impact of the symptoms in response to treatment. These variables with increased strength include dissatisfaction with weight and shape, BMI, shape concerns, eating concerns, binge eating, and depressive symptoms (Forrest & Grilo, 2022;Forrest, Franko, Thompson-Brenner, & Grilo, 2023;Hilbert et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal psychotherapy: It can help reduce binge eating triggered by bad communication abilities and relationships [108][109][110].…”
Section: Eating Disorder Treatments (Non-drug) Medicationsmentioning
confidence: 99%